1940
DOI: 10.1113/expphysiol.1940.sp000831
|View full text |Cite
|
Sign up to set email alerts
|

The Site of Action of Thyroxin on Water‐metabolism

Abstract: 1. Kidneys originating from thyroxinised dogs, when transplanted simultaneously with control kidneys to a donor anæsthetised with chloralosane, have been found to secrete more rapidly and to give larger responses to saline infusion and to hypophysectomy than the controls. 2. The method adopted and the results obtained demonstrate that the diuretic effect of thyroxin is due, at least in part, to a direct action on the kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1941
1941
1975
1975

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Theories proposed to explain this defect include accelerated destruction of vasopressin or resistance of the distal nephron to its effects [66,143], reduced medullary sodium concentration secondary to increased medullary blood flow [34], and perhaps osmotic diuresis due to increased filtered solute [84], It is possible, however, that mild degrees of concentrating impairment could simply be caused by alterations in the level of ionized calcium in plasma and urine that are either transient or too small to be detected. Consistent with this postulate and the possibility of structural lesions which may persist in a euthyroid environment, is the in triguing but unconfirmed observation that kidneys from thyroxin-treated dogs excrete more urine than kidneys from euthyroid animals when trans planted into normal dogs [22]. [43,90], Although the acute attack is usually accompanied by hypokalemia, the role of disturbed K metabolism in thyrotoxic periodic paralysis is not clear, since plasma K is normal between attacks and Ke is no different from that of thyrotoxic patients free of paral ysis [125].…”
supporting
confidence: 54%
“…Theories proposed to explain this defect include accelerated destruction of vasopressin or resistance of the distal nephron to its effects [66,143], reduced medullary sodium concentration secondary to increased medullary blood flow [34], and perhaps osmotic diuresis due to increased filtered solute [84], It is possible, however, that mild degrees of concentrating impairment could simply be caused by alterations in the level of ionized calcium in plasma and urine that are either transient or too small to be detected. Consistent with this postulate and the possibility of structural lesions which may persist in a euthyroid environment, is the in triguing but unconfirmed observation that kidneys from thyroxin-treated dogs excrete more urine than kidneys from euthyroid animals when trans planted into normal dogs [22]. [43,90], Although the acute attack is usually accompanied by hypokalemia, the role of disturbed K metabolism in thyrotoxic periodic paralysis is not clear, since plasma K is normal between attacks and Ke is no different from that of thyrotoxic patients free of paral ysis [125].…”
supporting
confidence: 54%
“…Studies upon water and electrolytes metabolism in thyrotoxicosis have been done by several authors (Byrom 1934;Boekelman, 1948;Cachera et al, 1949;Munro et al, 1958;Staffurth, 1962), though none of the report concerning actual determination of intracellular water and electrolytes has been published. Decrease of total and intracellular water content in muscles of thyrotoxicosis, proved in this study, may be related to increased sweating and insensible perspiration (Peters, 1944) or partly due to urinary excretion (Brull, 1940), though it may be reflected the direct effect by increased passive permeability of water across cell membrane by the thyroid hormone itself (Green and Matty, 1964). Fall of intracellular potassium in thyrotoxicosis, proved in biopsied muscle tissue, raised the question whether this is due to destruction of muscle cells in thyrotoxicosis which was infrequently encountered.…”
Section: Discussionmentioning
confidence: 99%
“…Brull (23) has demonstrated that the diuretic action of thyroxin is due, in part at least, to a direct action on the kidney rather than to an indirect influence through water mobilization from the body as a whole. He transplanted a kidney from a thyroxinized animal and one from a normal animal into the femoral vessels of a third.…”
Section: The Thyroidmentioning
confidence: 98%